2013
DOI: 10.1016/j.joca.2012.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylase inhibitors suppress mechanical stress-induced expression of RUNX-2 and ADAMTS-5 through the inhibition of the MAPK signaling pathway in cultured human chondrocytes

Abstract: The CTS-induced expression of RUNX-2 and ADAMTS-5 was suppressed by HDAC inhibitors via the inhibition of the MAPK pathway activation in human chondrocytes. The results of the current study suggested a novel therapeutic role for HDAC inhibitors against degenerative joint disease such as osteoarthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 51 publications
3
43
1
Order By: Relevance
“…It is also reported that the expression of RUNX-2 contributes to increased expression of MMP-13 [16]. Our previous report demonstrated that RUNX-2 is an upstream regulator of the mechanical stress-induced ADAMTS-5 and MMP-13 [22,25].…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…It is also reported that the expression of RUNX-2 contributes to increased expression of MMP-13 [16]. Our previous report demonstrated that RUNX-2 is an upstream regulator of the mechanical stress-induced ADAMTS-5 and MMP-13 [22,25].…”
Section: Discussionmentioning
confidence: 85%
“…Using this apparatus, the entire silicon membrane can be stretched uniformly [23,24]. In the current study, a CTS (0.5 Hz, 10 % elongation) was applied for 30 min as described in our previous study [22,25]. Cells incubated without mechanical stress were used as control.…”
Section: Stretching Experimentsmentioning
confidence: 99%
“…Chemical inhibition of HDAC activity could improve osteogenic differentiation, suggesting both a direct acetylation-dependent [16,18], as well as a MAPKinase-dependent mechanism [19]. There is evidence that several HDACs affect the expression and activity of the key osteogenic transcription factor Runx2.…”
Section: Introductionmentioning
confidence: 99%
“…Grb2 has been known to play a positive role in receptor tyrosine kinase signaling [24, 25], and the association of Grb2 and Shc/FAK is upstream to the activation of MAPK, which is an important signaling pathway leading to the proliferation and matrix synthesis of chondrocytes when exposed to periodic mechanical stress [26, 27]. We therefore hypothesized that the effect of Grb2 in mechanical signal transduction in chondrocytes may be related to the stimulation of MAPK pathway.…”
Section: Resultsmentioning
confidence: 99%